PENGARUH KUALITAS PELAYANAN, HARGA, DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PENGGUNAAN JASA PT POS INDONESIA PASAR JOHAR KOTA SEMARANG - Retno Candra Wahyuni; Handoyo Djoko Waloejo (Universitas Diponegoro, 2020)
Along with outgrowth the times that demands compliance the needs and needs of service users for package delivery, PT Pos Indonesia Johar Market Semarang City needs to do a marketing strategy, namely by improving the quality services offered by the company, pricing according to the services offered by the company, and the corporate image which will make service users make service usage decision. This study aims to determine the effect of service quality, price, and corporate image on service usage decisions of PT Pos Indonesia Johar Market Semarang City. This type of research is explanatory. The sampling technique uses a nonprobability sampling technique with the type of sampling used are incidental sampling and purposive sampling. The number of samples taken is 100 respondents who have made service usage decisions of PT Pos Indonesia Johar Market Semarang City. This research is testing using statistics with the help of IBM SPSS version 21.0 system. The results showed that service quality has a significant effect on service usage decisions by contributing 42.9%, price has a significant effect on service usage decisions by contributing 36.6%, and corporate image has a significant effect on service usage decisions by contributing 47,4%. While the rest is influenced by other factors besides service quality, price, and corporate image. Based on the calculation of the F Test shows that service quality, price, and corporate image significant influence on service usage decision.